CONSULTATION ON AFRICAN CHURCH MUSIC (International Library of African Music, 1970)
The bi-annual Consultation on African church music was held by the Christian Academy at Roodekrans, near Johannesburg, South Africa on the 16-17 July, 1969, to discuss the development of music in the African church in South Africa.
Keywords: African Music